THE EFFECTS OF PREPARATORY MUSCLE ACTIVATION ON LOWER EXTREMITY BIOMECHANICS DURING A DOUBLE LEG DROP-JUMP TASK - Kim, Katie (My University, 2024)
Authors: Lauren Crawford and Katie Kim, Mentor: Dr. Anthony Kulas Background: Anterior Cruciate Ligament (ACL) injuries are widely known as the most common ligament injury of the knee, recently accounting for 100,000 to 200,000 of the total injury count for athletes each year. America spends on average $3,812,100,000 for ACL reconstructions yearly. Even with this surgery, there is a lack of evidence to prove that reconstruction prevents long-term joint damage such as osteoarthritis. To prevent these instances from occurring, biomechanical risk factors must be evaluated. A study focusing on the 2-dimensional analysis of dynamic knee valgus in athletes was performed (Numata et al., 2018). The results yielded by this study showed that 3 years after the first evaluation 9.6% of the athletes had sustained ACL injuries. The injured athletes had a greater knee valgus at initial contact with the ground than the non-injured athletes, showing knee valgus is a strong risk factor. It is hypothesized that hip muscle activation affects knee joint movements. Preparatory muscle activation happens before the actual movement i.e., before landing, making it plausible that appropriate preparatory hip muscle activation is a central component in reducing knee valgus. Purpose: The purpose of this study is to determine if hip muscle activation affects knee valgus during a vertical drop jump task. Methods: All subjects must be healthy meaning that they have not experienced any major lower extremity injuries. After completing the informed consent process, subjects will be prepped and set up for the use of electromyography (EMG). Electrodes will be attached to glute, quad, and hamstring, muscles. Each participant performed isometric hip abduction, hip extension, and knee flexion strength tests using a dynamometer. The subjects will then have reflective markers attached to major landmarks of the body to be used in motion capture analysis. Subjects are given 2 tasks to complete, squats and vertical drop jumps. Their movements are analyzed using both motion capture and EMG equipment. Results: The magnitude of pre-activation was not significantly different compared to post activation for the semitendinosus (P=.42), gluteus maximus (P=.46), and gluteus medius muscles (P=.17). Biceps femoris post-activation was significantly greater than pre-activation (P=.025), increasing activation from 77% to 93% on average. Gluteus medius pre-activation was significantly correlated with peak knee flexion angle during landing (r=.663, P=.01). Semitendinosus post activation was negatively correlated with peak knee valgus (r=-.58, P=.03). Significance: By understanding when hip activation happens during preparation for the jump, hip and knee torques can be better related to frontal knee motion, such as knee valgus, during the landing. If hip activation timing affects knee joint angles, interventions could be created to attempt a decrease in knee valgus and load, lowering the number of ACL tears as well as decreasing the population of young adults with osteoarthritis.
Keywords: EMG; Biomechanics; ACL